Graphene based nano scale heat spreader in field effect transistor - Ashrafi, Shafana; Ahnaf, Shekh Rafid; Promy, Tasfia (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.